Gold nanorod assembly based on Hough-Merster effect, preparation method and application
The polymer hydrophilicity of gold nanorods is regulated through the Hoff Mester effect, and the highly ordered orientation arrangement of gold nanorods is achieved, which solves the problem of uncontrollable optical properties of gold nanorods in the prior art, simplifies the preparation process and Suitable for industrial production, a variety of assembly materials with different optical properties have been obtained.
Patent Information
- Application Number
- CN202411308311.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to achieve highly orderly orientated arrangement of gold nanorods, resulting in uncontrollable optical properties, and the self-assembly method is complex and costly, making it difficult to meet the needs of industrial production.
By using a self-assembly method based on the Hoff Mester effect, the hydrophilic properties of the polymer grafted on the surface of the gold nanorod are regulated, and the concentration of different kinds of salt solutions is used to change the interaction of the gold nanorods to achieve a highly ordered By aligning, a gold nanorod assembly with controllable optical properties was prepared.
The highly orderly oriented arrangement of gold nanorods is realized, the preparation process is simplified, and industrial production is facilitated. Two-dimensional super-sized with smectic liquid crystal phase, two-dimensional film, smectic liquid crystal phase, three-dimensional film, and vertical hexagonal stacking are obtained. The lattice and vertical hexagonal stacked three-dimensional superlattice have adjustable optical properties.
Smart Images

Figure CN119187587A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material chemistry and optical material, and specifically relates to a gold nanorod assembly based on the Hofmeister effect, a preparation method and an application thereof. Background Art
[0002] Gold nanorods (AuNRs) are rod-shaped gold nanoparticles. Compared with isotropic spherical gold nanoparticles, gold nanorods have two surface plasmon resonance (SPR) absorption peaks, one in the transverse direction and the other in the longitudinal direction. Therefore, by controlling the aspect ratio of gold nanorods, the surface plasmon resonance characteristics can be precisely controlled, making them continuously adjustable from visible light to near-infrared light. However, due to the poor uniformity of the size and shape of individual gold nanorods, the SPR peak is usually sharp and the resonance mode is single. Studies have found that when gold nanorods are highly ordered and directional, the near-field coupling between nanorods can significantly enhance their surface plasmon resonance effect, which has important application prospects in the fields of biological detection, energy storage, fluorescence enhancement, etc. Therefore, constructing highly ordered and directional gold nanorod assemblies with controllable and adjustable optical properties is a current research hotspot and difficulty.
[0003] The self-assembly method based on "bottom-up" is considered to be one of the most promising strategies for achieving directional arrangement of gold nanorods. It mainly achieves an ordered assembly structure of gold nanorods with oriented behavior by regulating the weak interactions between gold nanorods during the assembly process. For example, CN106882764A reports a method for controllable assembly of gold nanorods based on antigen-antibody reaction, that is, antigen-antibody is directionally coupled to the end face or side face of the gold nanorod, and the directional arrangement of the gold nanorods is achieved through specific recognition between antigen-antibody. CN106882764A reports a method for preparing an aqueous gold nanorod assembly based on host-guest interaction, that is, the two ends and both sides of the gold nanorod are directional modified by organic guest molecules, thereby achieving controllable assembly of the gold nanorods. However, these assembly methods usually require strict directional modification of the sides and end faces of the gold nanorods, respectively, and the experimental operation is cumbersome, the economic cost is high, and it is difficult to meet industrial production. Summary of the invention
[0004] In view of this, in order to solve this problem, the present invention discloses a gold nanorod assembly based on the Hofmeister effect, a preparation method and an application thereof, which is a self-assembly method regulated by the Hofmeister effect, and the method is simple and easy to control, and is convenient for industrial production.
[0005] It should be noted that the Hofmeister Effect refers to the different abilities of different types of salts to precipitate proteins from aqueous solutions. In recent years, studies have found that certain types of anions (such as SO4 2- 、CO3 2- The water molecules of water-soluble polymers (such as water-soluble polymers) can be polarized to destroy the hydrogen bonding between water-soluble polymers and water molecules. By changing the type and concentration of anions, the hydrophilicity and hydrophobicity of water-soluble polymers can be precisely controlled. Therefore, this patent proposes a self-assembly method based on Hofmeister regulation, which precisely controls the interaction of gold nanorods by regulating the hydrophilicity and hydrophobicity of the polymer grafted on the surface of gold nanorods, and achieves a highly ordered directional arrangement of gold nanorods, thereby obtaining a gold nanorod assembly material with controllable and adjustable optical properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first object of the present invention is to provide a method for preparing a gold nanorod assembly based on the Hofmeister effect, comprising adding an inorganic salt solution to a gold nanorod solution; the volume ratio of the gold nanorod solution to the inorganic salt solution is 1:10-15; the inorganic salt solution is a soluble carbonate or a soluble sulfate, and the concentration of the inorganic salt solution is 0.30-0.70M.
[0008] Optionally, the soluble carbonate is potassium carbonate, sodium carbonate or ammonium carbonate, and the soluble sulfate is potassium sulfate, sodium sulfate, ammonium sulfate or magnesium sulfate.
[0009] Optionally, the gold nanorod solution is a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30-50 nM, and the specific preparation method is as follows:
[0010] According to the molar ratio of SH-PEG to AuNRs of 3000-5000:1, the thiol-modified polyethylene glycol solution was added to the AuNRs solution, vortexed for 1-3 min to mix evenly, and reacted at 25 °C for 12-24 h to obtain polyethylene glycol-modified gold nanorods (PEG@AuNRs);
[0011] The polyethylene glycol-modified gold nanorods (PEG@AuNRs) are centrifugally washed and then redispersed in deionized water to prepare a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30-50 nM.
[0012] Furthermore, the concentration of the AuNRs solution is 1 mM, the length of the gold nanorods (AuNRs) is 35.8±2.8 nm, the diameter is 8.9±0.7 nm, and the aspect ratio is 4.02.
[0013] It should be noted that other precious metal nanorods with different aspect ratios, such as gold nanorods, platinum nanorods, silver nanorods, palladium nanorods, etc., are also applicable to the technical scope claimed for protection in this case.
[0014] Furthermore, the concentration of the thiol-modified polyethylene glycol solution is 1.0-5.0 mM.
[0015] Optionally, an inorganic salt solution is added to the gold nanorod solution, vortexed for 1-3 minutes, and allowed to stand at room temperature in the dark for 2-3 days to obtain a gold nanorod self-assembly.
[0016] Specifically, the inorganic salt solution is preferably an aqueous potassium carbonate solution or an aqueous potassium sulfate solution, and the preferred concentrations of the aqueous potassium carbonate solution are 0.52M, 0.54M, 0.57M and 0.60M, and the preferred concentrations of the aqueous potassium sulfate solution are 0.48M, 0.50M, 0.54M, and 0.57M. By adding aqueous potassium carbonate solution or aqueous potassium sulfate solution of the above concentrations respectively, a two-dimensional thin film of a smectic liquid crystal phase, a three-dimensional thin film of a smectic liquid crystal phase, a two-dimensional superlattice of vertical hexagonal stacking, and a three-dimensional superlattice of vertical face-centered cubic.
[0017] The second object of the present invention is to provide a gold nanorod self-assembly prepared by the method as described above.
[0018] The gold nanorod self-assembly comprises a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacked two-dimensional superlattice and a vertical face-centered cubic three-dimensional superlattice.
[0019] The third object of the present invention is to provide a gold nanorod self-assembly prepared by the method as described above for use in biosensors, nano-optoelectronics and optical information storage.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention is based on a self-assembly method regulated by the Hofmeister effect. By simply changing the concentration of a salt solution to regulate the hydrophilicity and hydrophobicity of a water-soluble polymer on the surface of gold nanorods, a highly ordered directional arrangement of the gold nanorods is achieved, thereby obtaining a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacking two-dimensional superlattice film and a vertical hexagonal stacking three-dimensional superlattice. The preparation method is simple and easy to control, and is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0023] Figure 1 This is a scanning electron microscope image of a two-dimensional thin film of smectic liquid crystal phase.
[0024] Figure 2 This is a scanning electron microscope image of a three-dimensional thin film of a smectic liquid crystal phase.
[0025] Figure 3 This is a scanning electron microscope image of a vertically hexagonal stacked two-dimensional superlattice.
[0026] Figure 4 This is a scanning electron microscope image of a three-dimensional superlattice with vertical hexagonal stacking.
[0027] Figure 5 It is a graph of surface tension as a function of salt concentration.
[0028] Figure 6 (a) The ultraviolet absorption spectrum of monodisperse gold nanorods; (b) the ultraviolet absorption spectrum of smectic liquid crystal phase two-dimensional film, smectic liquid crystal phase three-dimensional film, vertical hexagonal stacking two-dimensional superlattice and vertical hexagonal stacking three-dimensional superlattice.
[0029] Figure 7 It is the experimental flow chart.
[0030] Figure 8 These are scanning electron microscope images of the smectic liquid crystal phase two-dimensional film (a), the smectic liquid crystal phase three-dimensional film (b), the vertical hexagonal stacking two-dimensional superlattice (c) and the vertical face-centered cubic three-dimensional superlattice (d) obtained in Example 5. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0033] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0034] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0035] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0036] The present invention discloses a gold nanorod assembly based on the Hofmeister effect, a preparation method and an application thereof. The gold nanorod assembly is a self-assembly method based on the Hofmeister effect. The hydrophilicity and hydrophobicity of a water-soluble polymer on the surface of the gold nanorods are regulated by simply changing the concentration of a salt solution, and the interaction of the gold nanorods is precisely controlled to achieve a highly ordered directional arrangement of the gold nanorods, thereby obtaining four gold nanorod assembly materials with different optical properties, namely, a two-dimensional thin film of a smectic liquid crystal phase, a three-dimensional thin film of a smectic liquid crystal phase, a two-dimensional superlattice of vertical hexagonal stacking, and a three-dimensional superlattice of vertical hexagonal stacking. Figure 7 ).
[0037] The specific operation method is as follows:
[0038] Step 1
[0039] First, gold nanorods (AuNRs) with a length of 35.8±2.8 nm, a diameter of 8.9±0.7 nm, and an aspect ratio of 4.02 were synthesized according to the existing seed growth method, and a 1 mM AuNRs solution was prepared for use.
[0040] Step 2
[0041] The solid powder of thiol-modified polyethylene glycol (number average molecular weight of 1000) is fully dissolved in deionized water to prepare a thiol-modified polyethylene glycol solution with a concentration of 1.0-5.0 mM.
[0042] Step 3
[0043] According to the molar ratio of SH-PEG to AuNRs of 3000-5000:1, the above polyethylene glycol solution was added to the AuNRs solution, vortexed for 1-3 minutes to mix evenly, and reacted at 25°C for 12-24 hours. Finally, polyethylene glycol-modified gold nanorods (PEG@AuNRs) were obtained by ligand exchange. In order to further remove excess polyethylene glycol, after three centrifugation (12000rpm, 15min) washing, it was redispersed in deionized water to prepare a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30-50nM.
[0044] Step 4
[0045] According to the volume ratio of PEG@AuNRs solution to inorganic salt aqueous solution of 1:10-15, potassium carbonate aqueous solution with concentrations of 0.52M, 0.54M, 0.57M and 0.60M or potassium sulfate aqueous solution with concentrations of 0.48M, 0.50M, 0.54M and 0.57M are added to the PEG@AuNRs solution obtained in step (3), vortexed for 1-3min, and allowed to stand at room temperature in the dark for 2-3 days, to obtain a large amount of smectic liquid crystal phase two-dimensional thin film, smectic liquid crystal phase three-dimensional thin film, vertical hexagonal stacking two-dimensional superlattice and vertical face-centered cubic three-dimensional superlattice.
[0046] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0047] Example 1
[0048] The method for preparing the smectic liquid crystal phase two-dimensional thin film is as follows:
[0049] (1) Gold nanorods (AuNRs) with a length of 35.8±2.8 nm, a diameter of 8.9±0.7 nm, and an aspect ratio of 4.02 were synthesized according to the existing seed growth method, and a 1 mM AuNRs solution was prepared for use.
[0050] (2) The solid powder of thiol-modified polyethylene glycol (number average molecular weight of 1000) was fully dissolved in deionized water to prepare a thiol-modified polyethylene glycol solution with a concentration of 1.0 mM.
[0051] (3) According to the molar ratio of SH-PEG to AuNRs of 5000:1, the above polyethylene glycol solution was added to the 30mM AuNRs solution, vortexed for 2min to mix evenly, and reacted at 25°C for 24h. Finally, polyethylene glycol-modified gold nanorods (PEG@AuNRs) were obtained by ligand exchange. In order to further remove the excess polyethylene glycol, after three centrifugation (12000rpm, 15min) washing, it was redispersed in deionized water to prepare a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30nM.
[0052] (4) Adding a 0.52 M potassium carbonate aqueous solution to the PEG@AuNRs solution obtained in step (3) in a volume ratio of 1:10 between the PEG@AuNRs solution and the inorganic salt aqueous solution, vortexing for 1-3 min, and standing at room temperature in the dark for 2-3 days to obtain a large amount of smectic liquid crystal phase two-dimensional thin film.
[0053] Example 2
[0054] The method for preparing a smectic liquid crystal phase three-dimensional multilayer film is as follows: basically the same as Example 1, the only difference is that in step (4), the obtained PEG@AuNRs solution is added to a potassium carbonate solution with a concentration of 0.54M.
[0055] Example 3
[0056] The method for preparing a vertical hexagonal stacked two-dimensional superlattice film is as follows: basically the same as Example 1, the only difference is that in step (4), the obtained PEG@AuNRs solution is added to a 0.57M potassium carbonate solution.
[0057] Example 4
[0058] The method for preparing a vertical face-centered cubic three-dimensional superlattice is as follows: basically the same as Example 1, except that in step (4), the obtained PEG@AuNRs solution is added to a 0.60 M potassium carbonate solution.
[0059] Example 5
[0060] The method is basically the same as Example 1, except that in step (4), 0.48 M, 0.50 M, 0.54 M and 0.57 M potassium sulfate aqueous solutions are added to the obtained PEG@AuNRs solution, respectively, to obtain a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacking two-dimensional superlattice and a vertical face-centered cubic three-dimensional superlattice, respectively.
[0061] Example 6
[0062] A method for preparing a smectic liquid crystal phase two-dimensional thin film, the steps are as follows:
[0063] (1) A 1 mM thiol-modified polyethylene glycol solution was added to a 1 mM gold nanorod (length 35.8±2.8 nm, diameter 8.9±0.7 nm, aspect ratio 4.02) solution, wherein the molar ratio of thiol-modified polyethylene glycol to gold nanorod was 3000:1, and the mixture was mixed and reacted at 25°C for 20 h to obtain PEG@AuNRs through ligand exchange;
[0064] (2) washing the polyethylene glycol-modified gold nanorods obtained in step (1) by centrifugation three times and dispersing them in deionized water to obtain a monodisperse PEG@AuNRs aqueous solution with a concentration of 35 nM;
[0065] (3) Adding a 0.48 M sodium sulfate aqueous solution to the PEG@AuNR solution obtained in step (2) in a volume ratio of 1:11 between the PEG@AuNR solution and the inorganic salt aqueous solution, vortexing for 1-3 min, and standing at room temperature in the dark for 2-3 days to obtain a large amount of smectic liquid crystal phase two-dimensional thin film.
[0066] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples and test examples are used to further illustrate the technical features disclosed in the present invention, but they should not be understood as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without creative work are also considered to fall within the scope of protection of the present invention.
[0067] Comparative Example 1
[0068] The method is basically the same as Example 1, except that in step (4), the obtained PEG@AuNRs solution is added to a 1 M potassium carbonate solution to obtain disordered aggregates.
[0069] Test example
[0070] 1) The microscopic morphology of the smectic liquid crystal phase two-dimensional film prepared in Example 1 was analyzed using a high-resolution scanning electron microscope. Figure 1 As shown. When the PEG@AuNRs assembly unit is placed in a 0.52M K2CO3 aqueous solution, carbonate ions begin to destroy the hydrogen bonds between water-soluble polyethylene glycol and hydrated water molecules, thereby expelling some water molecules from the polyethylene glycol molecular chains, causing the polyethylene glycol to gradually change from hydrophilic to hydrophobic. Under the weak hydrophobic interaction between polyethylene glycol molecular chains, the gold nanorods slowly approach each other in a lying manner, in order to reduce the surface energy of PEG@AuNRs, and finally assemble into a micron-level smectic liquid crystal phase two-dimensional film ( Figure 1 a) From Figure 1 b It can be clearly seen that the nanorods present a typical periodic arrangement of smectic liquid crystal phase in the single-layer film.
[0071] 2) The microscopic morphology of the smectic liquid crystal phase three-dimensional multilayer film prepared in Example 2 was analyzed using a high-resolution scanning electron microscope. Figure 2 As shown. Figure 2 It was found that when the potassium carbonate concentration increased from 0.52M to 0.54M, the gold nanorod assembly transformed from a two-dimensional monolayer to a three-dimensional multilayer film. Figure 2 a It can be clearly seen that the nanorods are still arranged periodically in a lying and shoulder-to-shoulder manner in the three-dimensional film. The main difference is that the film presents an obvious multi-layer regular structure. Figure 2 b The side view shows that the AuNR in the lying conformation is mainly assembled in parallel and side by side to form a multilayer structure that is almost parallel to each other. The multilayer film is composed of about three layers arranged in a periodic stack perpendicular to the length axis of the nanorods. This is mainly because when the concentration of potassium carbonate salt is increased, more carbonate ions have a greater ability to destroy the hydrogen bonds between polyethylene glycol and hydrated water molecules, thereby causing polyethylene glycol to transform to a stronger hydrophobic property. The nanorods tend to form a three-dimensional multilayer film with a smaller surface energy under the stronger hydrophobic effect of polyethylene glycol.
[0072] 3) The microstructure of the vertical hexagonal stacked two-dimensional superlattice film prepared in Example 3 was analyzed using a high-resolution scanning electron microscope. Figure 3 As shown. The study found that when the potassium carbonate concentration was further increased to 0.58M, the gold nanorods were mainly arranged vertically side by side. From the front view of the two-dimensional monolayer film ( Figure 3 a), gold nanorods present a highly ordered hexagonal stacking periodic arrangement in the film structure. From the side view of the two-dimensional monolayer film ( Figure 3 b), the film is a single-layer film, and the nanorods stand shoulder to shoulder in the film. The above results show that when the concentration of the salt solution is further increased to 0.58M, a large number of carbonate ions in the solution can destroy more hydrogen bonds between water-soluble polyethylene glycol and water molecules, thereby increasing the degree of polyethylene glycol's transformation to hydrophobicity, driving the nanorods to transition from a lying conformation to an upright conformation, and finally forming a two-dimensional single-layer superlattice film with a smaller surface energy and arranged vertically shoulder to shoulder.
[0073] 4) The microstructure of the vertical face-centered cubic three-dimensional superlattice prepared in Example 4 was analyzed using a high-resolution scanning electron microscope. Figure 4 As shown. Figure 4 a found that when the potassium carbonate concentration increased to 0.60M, a large number of three-dimensional superlattices with approximate hexagonal shapes were assembled. Figure 4b It can be clearly seen that the gold nanorods are still highly ordered in a vertical shoulder-to-shoulder manner, but the film presents a typical layer-by-layer assembly structure with a layer thickness of about tens of microns. This is because at this salt concentration, the greater hydrophobicity of polyethylene glycol drives the nanorods to assemble into a three-dimensional superlattice with minimum surface energy.
[0074] 5) The morphological structure of the various assembly structures prepared in Example 5 was analyzed using a high-resolution scanning electron microscope. The study found that when the potassium sulfate solution increased from 0.48M to 0.57M, a two-dimensional film of a smectic liquid crystal phase, a three-dimensional film of a smectic liquid crystal phase, a two-dimensional superlattice of vertical hexagonal stacking, and a vertical face-centered cubic three-dimensional superlattice were obtained in turn. Sulfate ions and carbonate ions play the same role, both of which can destroy the hydrogen bonds between water-soluble polymers and water molecules, and as the ion concentration increases, the degree of dehydration of the polymer ligands increases, thereby obtaining assembly structures with different orientations. The difference is that the dehydration ability of sulfate ions is stronger than that of carbonate ions. Therefore, the potassium sulfate concentration corresponding to the above four assemblies is lower than that of potassium carbonate.
[0075] The above experimental results show that the Hofmeister effect self-assembly strategy can guide the highly ordered directional arrangement of PEG@AuNRs, and based on the typical kosmotropic ions (such as carbonate ions and sulfate ions), they can polarize hydrated water molecules, thereby destroying the hydrogen bonding between water-soluble polymers and hydrated water molecules, and achieving polymer ligand dehydration. Therefore, the concentration of carbonate ions and sulfate ions plays a crucial role in the assembly process of nanorods, and different concentrations of carbonate ions and sulfate ions have different dehydration abilities for PEG ligands. High salt concentrations lead to strong hydrophobicity due to the strong dehydration ability of PEG ligands, while low salt concentrations lead to weak hydrophobicity of PEG due to its weak dehydration ability.
[0076] To quantitatively determine the hydrophobicity of PEG ligands at different salt concentrations, the interfacial tension (γ) of the toluene-salt solution interface was measured using a water contact angle meter. A high γ indicates a more hydrophilic PEG ligand, while a low γ indicates a more hydrophobic PEG ligand.
[0077] like Figure 5As shown in the figure, the γ of the salt droplet shows a sharp downward trend with the increase of salt concentration, which is attributed to the continuous increase in the degree of transformation of the PEG ligand from hydrophilic to hydrophobic. For example, in 0M K2CO3 solution, the hydrophilic PEG ligand produces the highest γ value (17.2mN / m). In 0.52M K2CO3 solution, the PEG ligand undergoes slight dehydration, resulting in a sharp drop in the γ value to 8.9mN / m. This is because the hydrophobic PEG ligand drives the nanorods to migrate to the two-phase interface, thereby significantly reducing the γ value of the droplet. This weaker hydrophobic interaction triggers the directional arrangement of the nanorods, ultimately forming a two-dimensional film of a smectic liquid crystal phase. When the salt concentration increases from 0.52 to 0.60M, the γ value decreases from 8.9 to 5.5mN / m, indicating that the hydrophobicity of the PEG ligand becomes stronger and stronger. In order to further reduce the surface energy, the nanorods assemble into a three-dimensional film of a smectic liquid crystal phase, a two-dimensional superlattice film with vertical hexagonal stacking, and a three-dimensional superlattice with vertical hexagonal stacking, respectively. However, when the salt concentration increased to 1.00 M (γ = 4.5 mN / m), strong dehydration induced the nanorods to rapidly form disordered aggregates. These results indicate that the self-assembly strategy assisted by ion-specific effects exhibits an extraordinary ability to finely guide the nanorods to tailor highly ordered superstructures.
[0078] In addition, an ultraviolet spectrophotometer was used to investigate the optical properties of the four gold nanorods prepared in the above examples.
[0079] like Figure 6 As shown in a, monodispersed gold nanorods usually have two typical absorption peaks, corresponding to the transverse and longitudinal surface plasmon resonance modes. Studies have found that the directional and ordered assembly of gold nanorods can provide tunable SPR properties. Figure 6 b It can be seen that the two-dimensional and three-dimensional films of smectic liquid crystal phase assembled by gold nanorods show obvious blue shift of longitudinal plasma band and red shift of transverse plasma band due to the coupling effect between the arrangement of gold nanorods. When the gold nanorods are assembled to obtain a two-dimensional superlattice film with vertical hexagonal stacking, due to the nearly perfect vertical arrangement of the gold nanorods in the two-dimensional film, only the transverse plasma band of the two-dimensional superlattice film is selectively excited. This widening and red shift of the transverse plasma band is mainly caused by the plasma coupling between the densely packed oriented gold nanorods. The three-dimensional superlattice with vertical hexagonal stacking will further aggravate the widening and red shift of the transverse plasma band.
[0080] It can be seen that the self-assembly method based on the regulation of the Hofmeister effect can construct ordered assemblies of gold nanorods with tunable SPR properties, providing new application avenues for fields such as nanophotonics and biomedical imaging.
[0081] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a gold nanorod assembly based on the Hofmeister effect, characterized in that: The method comprises adding an inorganic salt solution into a gold nanorod solution; the volume ratio of the gold nanorod solution to the inorganic salt solution is 1:10-15; the inorganic salt solution is a soluble carbonate or a soluble sulfate, and the concentration of the inorganic salt solution is 0.30-0.70M.
2. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 1, characterized in that: The soluble carbonate is potassium carbonate, sodium carbonate or ammonium carbonate, and the soluble sulfate is potassium sulfate, sodium sulfate, ammonium sulfate or magnesium sulfate.
3. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 1, characterized in that: The gold nanorod solution is a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30-50 nM, and the specific preparation method is as follows: According to the molar ratio of SH-PEG to AuNRs of 3000-5000:1, the thiol-modified polyethylene glycol solution was added to the AuNRs solution, vortexed for 1-3 min to mix evenly, and reacted at 25 °C for 12-24 h to obtain polyethylene glycol-modified gold nanorods (PEG@AuNRs); The polyethylene glycol-modified gold nanorods (PEG@AuNRs) are centrifugally washed and then redispersed in deionized water to prepare a monodisperse PEG@AuNRs aqueous solution with a molar concentration of 30-50 nM.
4. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 3, characterized in that: The concentration of the AuNRs solution is 1 mM, the length of the gold nanorods (AuNRs) is 35.8±2.8 nm, the diameter is 8.9±0.7 nm, and the aspect ratio is 4.
02.
5. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 3, characterized in that: The concentration of the thiol-modified polyethylene glycol solution is 1.0-5.0 mM.
6. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 1, characterized in that: An inorganic salt solution is added to the gold nanorod solution, the solution is vortexed for 1-3 minutes, and the solution is allowed to stand at room temperature in the dark for 2-3 days to obtain a gold nanorod self-assembly.
7. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 6, characterized in that: The inorganic salt solution is a potassium carbonate aqueous solution. Potassium carbonate aqueous solutions with concentrations of 0.52M, 0.54M, 0.57M and 0.60M are added to the gold nanorod solution respectively, and the solution is vortexed for 1-3 minutes and allowed to stand at room temperature in the dark for 2-3 days to obtain a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacking two-dimensional superlattice and a vertical face-centered cubic three-dimensional superlattice.
8. The method for preparing a gold nanorod assembly based on the Hofmeister effect according to claim 6, characterized in that: The inorganic salt solution is a potassium sulfate aqueous solution. Potassium sulfate aqueous solutions with concentrations of 0.48M, 0.50M, 0.54M, and 0.57M are added to the gold nanorod solution, respectively, and the solution is vortexed for 1-3 minutes and allowed to stand in the dark at room temperature for 2-3 days to obtain a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacking two-dimensional superlattice, and a vertical face-centered cubic three-dimensional superlattice.
9. A gold nanorod self-assembly prepared by the method according to claim 1, characterized in that: The gold nanorod self-assembly comprises a smectic liquid crystal phase two-dimensional film, a smectic liquid crystal phase three-dimensional film, a vertical hexagonal stacking two-dimensional superlattice and a vertical face-centered cubic three-dimensional superlattice.
10. Application of the gold nanorod self-assembly prepared by the method according to claim 1 in biosensors, nano-optoelectronics and optical information storage.
Citation Information
Patent Citations
Preparation method for aqueous phase gold nanorod assembly based on subject-object interaction
CN106882764A
Cited By
Surface-enhanced Raman substrate based on gold nanorod self-assembly and nanosphere photoetching as well as preparation method and application of surface-enhanced Raman substrate
CN120195147A
